Walka bez cienia nadziei : powstanie w getcie warszawskim - Gutman, Israel; Stopa, Marcin (Warszawa : Oficyna Wydawnicza Rytm, 1998)
A history of the uprising in the Warsaw Ghetto in 1943.
Translation of: Resistance : the Warsaw Ghetto uprising
Includes bibliographical references (p. 327-329) and index.
Keywords: Jews -- Persecutions -- Poland -- Warsaw; Holocaust, Jewish (1939-1945) -- Poland -- Warsaw; Warsaw (Poland) -- History -- Warsaw Ghetto Uprising, 1943.; Warsaw (Poland) -- Ethnic relations